Psychosis and the Desire for Externalization in the Individual Psyche and Neo‐Liberal Society. (25th July 2019) - Morgan, David
Abstract : Psychoanalysts have written about working with psychotic and severely disturbed people, but most of this work comes from the 1970s. Since then, there has been a notable absence of this pioneering clinical work. Reflecting on why this may have occurred, the author also suggests that many of these valuable theories around psychosis and its causes, such as trauma or unrecognized trans‐generational pain, are applicable to some of the current political and social malaise that confronts our time.